Recycling ash into the first stage of cyclone pre-heater of cement kiln. (October 2016) - Zhan, Ming-Xiu; Fu, Jian-Ying; Havukainen, Jouni; Chen, Tong; Li, Xiao-Dong; Yan, Jian-Hua; Buekens, Alfons
Highlights: The recycling fly ash would not promote the formation of PCDD/Fs. Raw meal has a tendency to reduce the formation of PCDD/Fs. The metal catalyst was the main influencing factor. The formation mechanism would be the de novo and precursor synthesis. Abstract: Fly ash collected from the bag filter could be recycled into the first stage of the cyclone pre-heater of the cement kiln, resulting in the possible enrichment of polychlorinated dibenzo- p -dioxins and dibenzofurans (PCDD/Fs). In this study, soxhlet fly ash (SFA) and raw meal (RM) were selected as the basis for the PCDD/F formation experiments. The levels of 2, 3, 7, 8-PCDD/Fs formed on the SFA and RM were observed to be 2550 pg/g (157 pg I-TEQ/g) and 1142 pg/g (55 pg I-TEQ/g), respectively. While less 2, 3, 7, 8-PCDD/Fs was detected when SFA was mixed with RM, suggesting that recycling cement kiln ash would not largely increase the concentration of PCDD/Fs in flue gas. Furthermore, the possible influencing factors on the PCDD/F formation were also investigated. The formation of 2, 3, 7, 8-PCDD/Fs was up to 10, 871 pg/g (380 pg I-TEQ/g) with the adding of CuCl2, which was much higher than the results of CuO and activated carbon. Most importantly, the homologue, congener and gas/particle distribution of PCDD/Fs indicated that de novo synthesis was the dominant PCDD/F formation pathway for SFA. Lastly, principal component analysis (PCA) was also conducted to identify the relationship between the compositions of reactant and the properties of PCDD/Fs produced.